Penerapan IFRS S1 dan S2 pada Sustainability Reporting PT PLN (Persero) - Simorangkir, Ricky Reagen Julius; Shauki, Elvia Rosantina (E-Jurnal Akuntansi; Vol 34 No 7 (2024), 2024)
Pressure from investors regarding non-financial information, environmental, social and governance issues is the main focus behind the implementation of IFRS S1 and S2 in PT PLN's sustainability reporting. The analysis used is in the form of a case study with data from observation, documentation and interviews using content and thematic analysis. The results show that in implementing IFRS S1 and S2 PT PLN publishes sustainability reports, ESG performance reports and TCFD reports, aiming to provide useful information for investors in decision making. PT PLN also aligned the core content of the ESG performance report with IFRS S1 and the TCFD report with IFRS S2. Challenges faced in implementing IFRS S1 and S2 include: meeting investor expectations regarding climate-related information presented, connectivity of the ESG Performance Report with financial statements, as well as targets for submitting IFRS S1 and S2 reporting simultaneously with financial reports. Keywords: IFRS S1 and S2, sustainability report, ESG performance report, TCFD report